Pola Komunikasi Antar Pribadi Dokter dan Pasien RSJ Bina Atma dalam Menghindari Resiko Peningkatan Gangguan Jiwa - Firla Salsabila Hasibuan (JURNAL SYIAR-SYIAR, 2024)
This research examines interpersonal communication patterns between doctors and patients at RSJ Bina Atma, as well as the role of this communication in avoiding the risk of increasing mental disorders. This study uses a qualitative approach with in-depth interview methods with doctors. The research results show that effective communication patterns, which involve empathy, openness, and an individual approach, have a significant influence in building patient trust and comfort. Doctors who are able to listen actively and provide appropriate responses can help reduce patient anxiety and stress, thereby preventing worsening of their mental condition. This finding is the importance of communication training for medical personnel in an effort to improve the quality of care and patient welfare at RSJ Bina Atma.